Jokers wild : legalized gambling in the twenty-first century - Barker, Thomas (Praeger, 2000)
A history and analysis of gambling in the United States from Bingo to state lotteries to Indian gaming and the rise of Las Vegas. The book reveals how America has become a nation of gamblers and what the future holds for the gambling industry.